TAFSIR AYAT-AYAT DAKWAH DI TENGAH TRADISI LOKAL, PRAKTIK DI KAMPUNG PAGELARANG LUBANG BUAYA JAKARTA TIMUR - Luqman (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
Islamic da‘wah cannot be separated from the social and cultural context of the society in which it takes place. Kampung Pagelarang, Lubang Buaya, East Jakarta, is an urban community that continues to preserve local traditions in its religious life. This study aims to analyze the practice of Islamic da‘wah amid local traditions in the Kampung Pagelarang community from the perspective of Qur’anic exegesis. The research employs a qualitative method with a thematic (maudhu‘i) tafsir approach and a field study based on the living Qur’an paradigm. Data were collected through participatory observation, in-depth interviews with religious leaders and community members, and documentation of religious activities. The findings indicate that the da‘wah model implemented is cultural and persuasive in nature, utilizing local traditions as a medium for internalizing Qur’anic values. The interpretation of da‘wah-related verses emphasizes the importance of the hikmah and mau‘izhah hasanah approaches in conveying Islamic messages within cultural diversity. This study concludes that local traditions can synergize with Islamic da‘wah as long as they do not contradict the principles of tawhid and Islamic law, and that da‘wah-oriented Qur’anic interpretation plays a strategic role in guiding the development of moderate and contextual cultural da‘wah.